Public finance and public policy - Jonathan Gruber (New York : Worth Publishers, 2023)
The book quickly became the market-leading text for Public Finance and Public Policy courses, and the margin is growing. Thoroughly updated, this timely new edition gives students the basic tools they need to understand the driving issues of public policy today, including healthcare, education, global climate change, entitlements, and more.